2010
DOI: 10.3923/pjbs.2010.362.368
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Antioxidant, Xanthine Oxidase and Acetylcholinesterase Inhibitory Activities of Balanites aegyptiaca (L.) Del. (Balanitaceae)

Abstract: The present study aimed to test the validity of Balanites aegyptiaca remedies used for the treatment of rheumatisms and mental disorders by examining the antioxidant, xanthine oxidase and acetylcholinesterase inhibitory activities of galls and leaves extracts and fractions. The total phenolics and flavonoids were measured using Folin-Ciocalteu and AlCl3 reagents, respectively. Two methods i.e., FRAP and ABTS were used to estimate the total antioxidant capacity of the plant materials. The FRAP and ABTS antioxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 27 publications
0
35
0
Order By: Relevance
“…The above differences in GPx activity could be related to the species and pathogenicity of the parasite and species of the animal. On the contrary to G1 and G3 animals, G2 (infected-BAF-EE-treated) and G4 (BAF-EEtreated only) goats revealed significant elevation in GPx activity which could be attributed to the BAF-EE antioxidant effect [9,71]. Antioxidant enzymes superoxide dismutase and catalase were elevated in mice treated with different parts of B. aegyptiaca extracts [72].…”
Section: Discussionmentioning
confidence: 98%
“…The above differences in GPx activity could be related to the species and pathogenicity of the parasite and species of the animal. On the contrary to G1 and G3 animals, G2 (infected-BAF-EE-treated) and G4 (BAF-EEtreated only) goats revealed significant elevation in GPx activity which could be attributed to the BAF-EE antioxidant effect [9,71]. Antioxidant enzymes superoxide dismutase and catalase were elevated in mice treated with different parts of B. aegyptiaca extracts [72].…”
Section: Discussionmentioning
confidence: 98%
“…The study also showed that B. aegyptiaca galls and leaves fractions exhibited a moderate xanthine oxidase inhibitory activity compared with the acetylcholinesterase which was weakly inhibited by the tested extracts and fractions. [88]…”
Section: Pharmacological Activitymentioning
confidence: 99%
“…The assay mixture was incubated at 25 ºC for 30 min. The reaction was stopped by adding 1 mL of 1 N HCl and the absorbance was measured at 290 nm using an UV spectrophotometer (19, 20). Allopurinol (5 – 100 μg/mL) was used as the standard.…”
Section: Methodsmentioning
confidence: 99%